Answer:
-2, 1, 6 and the 10th is 97
Explanation:
to find the terms, in a row, replace n with 1
nth = 1^2 -3 -2 is the answer (1^2) is 1 -3 = -2
then replace the n with 2, 3, 4 etc till you have your sequence
nth = 2^2 -3 1 is the answer (2^2) is 4 -3 = 1
nth = 3^2 -3 6 is the answer (3^2) is 9-3 = 6
nth = 4^2 -3 13 is the answer (4^2) is 16-3 = 13
nth = 5^2 -3 22 is the answer (5^2) is 25-3 = 22
etc to 10
nth = 10^2 -3 97 is the answer (10^2) is 100 - 3 = 97
sequence is -2, 1, 6, 13, 22, . . . . 97